1992
DOI: 10.1073/pnas.89.14.6653
|View full text |Cite
|
Sign up to set email alerts
|

Drug binding to higher ordered DNA structures: netropsin complexation with a nucleic acid triple helix.

Abstract: We have used a combination of spectroscopic and calorimetric techniques to characterize how netropsin, a ligand that binds in the minor groove of DNA, influences the properties of a DNA triple helix. Specifically, our data allow us to reach the following conclusions: (i) netropsin binds to the triplex without displacing the major-groove-bound third strand; (ui) netropsin binding to the triplex exhibits a lower saturation binding density (7.0 base triplets per netropsin bound) than netropsin binding to the corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
54
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 37 publications
(37 reference statements)
15
54
1
Order By: Relevance
“…Similar results were observed by Park et a!. 10 for dT · dA · dT triplex, each strand having 101 bases (202 base pairs). In their studies the influence ofnetropsin binding in the minor groove of DNA triplex ( Figure 2) was characterized by using spectroscopic and calorimetric techniques.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Similar results were observed by Park et a!. 10 for dT · dA · dT triplex, each strand having 101 bases (202 base pairs). In their studies the influence ofnetropsin binding in the minor groove of DNA triplex ( Figure 2) was characterized by using spectroscopic and calorimetric techniques.…”
supporting
confidence: 78%
“…4 • 9 -11 • 18 -20 Recently, Plum et al 9 and Park et al 10 reported spectroscopic and calorimetric studies on the DNA triplexes made of Yl5 · U21 · Y21. Here U and Y stand for purine and pyrimidine strands, the subscripts stand for the number of bases (30 and 42 base pairs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Netropsin binds to the minor groove of A⅐T pairs, requiring four or more such bp for optimal contacts, introduces additional negative supercoils, destabilizes triplex DNA, and increases the stiffness of the double helix (26,(51)(52)(53)(54)(55)(56)(57)(58). We reasoned that netropsin would accentuate cell loss in two ways.…”
Section: Pkd1 Unusual Dna Conformations Are Genotoxic In E Colimentioning
confidence: 99%
“…The 285 nm maximum is at too long a wavelength for the molecule to be adopting an A-DNA conformation, and the spectra do not contain a positive peak at around 205 nm, which would be expected if the tract were adopting duplex B-DNA structure (29 -31). The negative peak at 208 nm suggests that the tract has triplex character, as a negative peak between 200 and 220 nm is considered a hallmark of triplex DNA (29,30,32). Spectra for triplexes are usually able to be approximated as the sum of the CD for the component duplex and singlestranded DNA plus some extra intensity due to the more rigid structure (33).…”
Section: Resultsmentioning
confidence: 99%